PENGEMBANGAN TERMOMETER GAS SEBAGAI ALAT PERAGA PEMBELAJARAN POKOK BAHASAN SKALA SUHU MUTLAK - Aminoto, Tugiyo; Dani, Rahma; Yuversa, Edi (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2019)
The constant volume type gas thermometer has an important role as a learning medium that can help students understand the concept of absolute temperature more easily and concretely. Considering that this tool is difficult to find in the market, it is necessary to make an effort to make and develop the tool. The purpose of this development research is to produce a product in the form of a fixed volume type gas thermometer that is better than the existing one. The research method used is research development that includes research and data collection, planning, developing product drafts, developing learning materials, learning processes, and evaluation instruments, initial field trials, field trials, refining product field test results, perfecting final products and implementation.